2022
DOI: 10.1016/j.ejim.2022.01.035
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary embolism severity and in-hospital mortality: An international comparative study between COVID-19 and non-COVID patients

Abstract: Objective To compare the severity of pulmonary embolism (PE) between patients with and without COVID, and to assess the association between severity and in-hospital-mortality. Methods We performed an analysis of 549 COVID (71.3% PCR-confirmed) and 439 non-COVID patients with PE consecutively included by 62 Spanish and 16 French emergency departments. PE-severity was assessed by size, the presence of right ventricular dysfunction (RVD), and the sPESI. The association of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
0
12
1
Order By: Relevance
“…Our results show that although severity markers, including sPESI score, the need for mechanical ventilation, or a longer length of stay, were more frequent in COVID patients, in-hospital mortality was lower. These results disagree with the previous analysis of the SIESTA and PEPCOV research teams [ 16 ]. In this study conducted by Miró et al in 62 Spanish and 16 French hospitals, the in-hospital mortality was higher in COVID patients.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results show that although severity markers, including sPESI score, the need for mechanical ventilation, or a longer length of stay, were more frequent in COVID patients, in-hospital mortality was lower. These results disagree with the previous analysis of the SIESTA and PEPCOV research teams [ 16 ]. In this study conducted by Miró et al in 62 Spanish and 16 French hospitals, the in-hospital mortality was higher in COVID patients.…”
Section: Discussioncontrasting
confidence: 99%
“…Studies have evaluated the usefulness of the PESI scale in the context of PE secondary to COVID-19. Miró et al 21 showed a higher mortality in patients with PE secondary to COVID-19 compared to PE not secondary to COVID-19 (12.8 vs 5.3%, p < 0.001). Their results suggest an underestimation of in-hospital mortality with different scores on the sPESI scale (simplified PESI) in patients with PE secondary to COVID-19 compared to PE not caused by COVID-19 (sPESI 0 p = 0.003, sPESI 1 p = 0.028, sPESI, 2 p = 0.012, sPESI>2 p = 0.055).…”
Section: Discussionmentioning
confidence: 95%
“…If PE or DVT was diagnosed, all patients were treated with therapeutic anticoagulation, if no contraindications existed. Miró et al showed in a recent published study, that PE in COVID-19 patients was associated with less severity than in Non-COVID patients [38] . This could also be an explanation for the missing relevance of PE for mortality in our cohort.…”
Section: Discussionmentioning
confidence: 96%